2004
DOI: 10.1039/b314007e
|View full text |Cite
|
Sign up to set email alerts
|

Modeling microflow and stirring around a microrotor in creeping flow using a quasi-steady-state analysis

Abstract: The microflow and stirring around paramagnetic particle microchains, referred to as microrotors, are modeled as a circular cylinder rotating about its radial axis at very low Reynolds number. Time scales for momentum transfer under these conditions are determined to be much smaller than those for boundary movement, hence a quasi-steady approximation can be used. The flow is derived at every instant from the case of a steady motion of a horizontally translating cylinder, with the rotation approximated to a seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…To understand the dynamic behavior of the chains in more detail, models have been developed in which particle chains were treated as three-dimensional circular cylinders, 38 as chains of circles in two dimensions 17,39 and finally as chains of spheres in three dimensions. [40][41][42][43] To characterize the chain behavior, most studies 17,39,40,44 used the dimensionless Mason number, which is the ratio between the rotational shear forces (i.e.…”
Section: Mixing a Static Fluid Using Magnetic Particlesmentioning
confidence: 99%
“…To understand the dynamic behavior of the chains in more detail, models have been developed in which particle chains were treated as three-dimensional circular cylinders, 38 as chains of circles in two dimensions 17,39 and finally as chains of spheres in three dimensions. [40][41][42][43] To characterize the chain behavior, most studies 17,39,40,44 used the dimensionless Mason number, which is the ratio between the rotational shear forces (i.e.…”
Section: Mixing a Static Fluid Using Magnetic Particlesmentioning
confidence: 99%
“…This vertical flow contributes to the oxygen mass transportation from the top PDMS membrane to the DO sensor located at the bottom of the reactor. Vuppu et al (2004) also simulated the rotation of a mm-scale rotor; but their rotational flow is in the regime of very low Reynolds number (maximal Re n of $0.05) and viscous forces dominate over inertial forces with poor mixing as the consequence. Flow in the present microbioreactor has a significantly higher Reynolds number (Re n of 30$130) and the convective inertial force dominates in this laminar and transitional flow regime.…”
Section: Mixing and Oxygenationmentioning
confidence: 99%
“…In addition, capture and formation of supraparticle structures, modulation strategies (magnetic field strength and frequency or complex waveform), and signal capture and processing (or image analysis) can all dramatically impact the performance of the technique. Capture and formation strategies have been discussed elsewhere, in some depth, 31,33,34,[36][37][38][39][40][41][42][43][44] whereas frequency or complex waveform strategies for modulation have not been addressed yet.…”
Section: Modulated Competitive Myoglobin Assaymentioning
confidence: 99%
“…Existing flow-cell technologies have shown that containment and rotation of these structures is possible using a cell with a chamber volume of 5.3 nL. 38 Further development and incorporation of all of these technologies into a device would allow rapid analysis of serum samples leading to quicker AMI diagnosis.…”
Section: Fully Exploiting Modulated Immunoassaysmentioning
confidence: 99%